2017
DOI: 10.1007/s11250-017-1480-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary energy and protein levels on body weight, size, and microflora of ostrich chicks

Abstract: The aim of this study was to evaluate the effect of different dietary energy and protein supplements on performance, weekly body sizes or body frame size, and microbiota of ostrich chicks during 2–9 weeks of age. Two metabolic energy levels of 2400 and 2600 kcal/kg live weight and three protein levels of 20, 22, and 24% were used. A total of 36 ostrich chickens (Struthio camelus) of the blue and black African breed were used. Body weight, 12 body measurements (i.e., circumference of the head, neck, breast, abd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
(13 reference statements)
1
6
0
1
Order By: Relevance
“…The results of this study with regard to protein content of diets confirm the findings of others (Brand et al 2003 ; Brand, Nel & Van Schalkwyk 2000 ; Gandini, Burroughs & Ebedes 1986 ; Nikravesh-Masouleh et al 2018 ; Swart & Kemm 1985 ) that different levels of protein within certain ranges and above minimum levels for the growth phase in ostrich diets did not have a significant effect on the growth rate (live weight increase over time) or body measurements. Mahrose et al ( 2015 ) and Abd El-Hack and Amer (2019) concluded that young ostrich chicks (pre-starter) can grow on relatively low crude protein content diets of 18%, which is between the lowest levels, 1 and 2, of protein content in this study.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results of this study with regard to protein content of diets confirm the findings of others (Brand et al 2003 ; Brand, Nel & Van Schalkwyk 2000 ; Gandini, Burroughs & Ebedes 1986 ; Nikravesh-Masouleh et al 2018 ; Swart & Kemm 1985 ) that different levels of protein within certain ranges and above minimum levels for the growth phase in ostrich diets did not have a significant effect on the growth rate (live weight increase over time) or body measurements. Mahrose et al ( 2015 ) and Abd El-Hack and Amer (2019) concluded that young ostrich chicks (pre-starter) can grow on relatively low crude protein content diets of 18%, which is between the lowest levels, 1 and 2, of protein content in this study.…”
Section: Discussionsupporting
confidence: 91%
“…It is worth noting that in contrast, Tasirnafas et al ( 2015 ) evaluated the effect of different levels of dietary vegetable wastage and energy on ostrich chicks and found that energy level (10.5 and 11.3 MJ/kg) had no effect on feed intake, weight gain or feed efficiency. More recently, Nikravesh-Masouleh et al ( 2018 ) found that increasing energy and protein levels led to decreased weight gain in ostrich chicks (2–9 weeks of age). They found that the most important parameters at 9 weeks of age, such as breast, abdomen and thigh circumference as well as body length, were higher in birds that were fed the lower energy content diet (10.1 MJ/kg) as supposed to a higher energy diet (10.9 MJ/kg), although greater tail length and shank circumference were observed in birds that were fed the higher energy diet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, high‐fat diets (HFDs) have been commonly used to induce obesity in avian species (Recena Aydos et al., 2019). It has been shown that HFD in broilers and layer hens is associated with weight gain, dyslipidaemia and high‐fat accumulation in body tissues (Nikravesh‐Masouleh et al., 2018). Meleg et al., (2000) reported that 2,850 kcal/kg is a standard and suitable dietary energy for optimal growth and health status in pigeons.…”
Section: Introductionmentioning
confidence: 99%
“…All breeding programs for animals, including poultry, are aimed at improving breeding traits, either through genetics (Kawka et al 2010, 2012) or, for example, nutrition (Nikravesh-Masouleh et al 2018; Tasirnafas et al 2015). All of these treatments were aimed at increased body weight gain, growth rate, and conversion efficiency in poultry.…”
Section: Introductionmentioning
confidence: 99%